Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric device
Patent Information
- Application Number
- CN202510021774.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-05-09
AI Technical Summary
The existing multivariate positive electrode materials have shortcomings in improving the rate performance and cycle performance of batteries, especially in the grading method of small single crystal particles and large polycrystalline particles, it is difficult to exert both the rate and cycle performance.
Three or more positive electrode active materials of different particle sizes are used, including the first polycrystalline particles, the first single crystal particles, the second polycrystalline particles and the second single crystal particles, and the positive electrode active material with a high capacity is mixed by a specific mass ratio relationship (70%≤(m1+m2)/(m1+m2+m3)≤90%; 1%≤m2/(m1+m2)≤99%).
Through this combination, the rate performance and cycle performance of the battery are improved, the demand for fast charging and discharge is met, and the compaction density and energy density of the cathode material are improved.
Smart Images

Figure CN119965239A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art In the cathode material, the mixing of large and small particles is a currently used technical solution to improve the compaction density of the electrode. The conventional grading method is two-component grading, and large particles use polycrystalline. When single crystal small particles are used for grading, it is not conducive to the performance of the rate performance; when polycrystalline small particles are used, the cycle performance is greatly affected. Summary of the invention
[0002] In view of the problem that existing multi-element positive electrode materials are not conducive to improving battery rate performance or cycle performance, the present invention provides a positive electrode active material and a preparation method, a positive electrode plate and a battery.
[0003] The technical solution adopted by the present invention to solve the above technical problems is as follows: A first aspect of the present invention provides a positive electrode active material, comprising at least one of a first polycrystalline particle, a first single crystal particle, a second polycrystalline particle, and a second single crystal particle; The particle size of the second polycrystalline particles is 0.10 to 0.99 of the particle size of the first polycrystalline particles; The particle size of the second single crystal particles is 0.10 to 0.99 of the particle size of the first single crystal particles.
[0004] Optionally, the particle size of the first polycrystalline particles is 8-20 μm; the particle size of the first single crystal particles is 2-6.5 μm.
[0005] Optionally, the particle size of the second polycrystalline particles is 0.35 to 0.95 of the particle size of the first polycrystalline particles; and the particle size of the second single crystal particles is 0.7 to 0.9 of the particle size of the first single crystal particles.
[0006] Optionally, the positive electrode active material includes positive electrode active material A, and the positive electrode active material A includes the first polycrystalline particles, the second polycrystalline particles and the first single crystal particles, the mass of the first polycrystalline particles is m1, the mass of the second polycrystalline particles is m2, and the mass of the first single crystal particles is m3, and m1, m2, and m3 satisfy the relationship: 70%≤(m1+m2) / (m1+m2+m3)≤90%; 1%≤m2 / (m1+m2)≤99%.
[0007] Optionally, the positive electrode active material includes positive electrode active material B, and the positive electrode active material B includes the first polycrystalline particles, the first single crystal particles and the second single crystal particles, the mass of the first polycrystalline particles is m4, the mass of the first single crystal particles is m5, and the mass of the second single crystal particles is m6, and m4, m5, and m6 satisfy the relationship: 70%≤m4 / (m4+m5+m6)≤90%; 1%≤m6 / (m5+m6)≤99%.
[0008] Optionally, the positive electrode active material includes positive electrode active material C, and the positive electrode active material C includes the first polycrystalline particles, the first single crystal particles, the second single crystal particles and the second polycrystalline particles, the mass of the first polycrystalline particles is m7, the mass of the second polycrystalline particles is m8, the mass of the first single crystal particles is m9, and the mass of the second single crystal particles is m10, and m7, m8, m9 and m10 satisfy the relationship: 70%≤(m7+m8) / (m7+m8+m9+m10)≤90%; 1%≤m7 / (m7+m8)≤99%; 1%≤m9 / (m9+m10)≤99%.
[0009] Optionally, the positive electrode active material also includes supplementary particles, the particle size of the supplementary particles is different from the particle size of the first polycrystalline particles, the first single crystal particles, the second polycrystalline particles and the second single crystal particles. Taking the total mass of the positive electrode active material as 100%, the supplementary particles account for 1%-30% of the mass of the positive electrode active material.
[0010] Optionally, the first polycrystalline particles, the first single crystal particles, the second polycrystalline particles, the second single crystal particles and the supplementary particles are all ternary positive electrode active materials, and the ternary positive electrode active materials include one or more of lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide.
[0011] Optionally, the chemical formula of the lithium nickel cobalt manganese oxide is Li 1+a Ni x Co y Mn z O 2 , where a, x, y, and z satisfy the relationship: x+y+z=1; -0.1 <a<0.2。
[0012] Optionally, the positive electrode active material further includes a doping element and a coating element, wherein the doping element is mixed with the ternary positive electrode active material and doped inside the ternary positive electrode active material, and the coating element is coated outside the ternary positive electrode active material.
[0013] Optionally, the element doping includes one or more of Al, B, Ba, Bi, Ca, Cr, Ce, Co, Er, Ga, Ge, Ho, K, La, Mg, Mo, Na, Nb, Pd, Si, Sb, Sr, Se, Ru, Rh, Ta, Te, Ti, W, V, Y, Zr and Zn.
[0014] Optionally, the coating elements include one or more of Al, B, Ba, Bi, Ca, Cr, Ce, Co, Er, Ga, Ge, Ho, K, La, Mg, Mo, Na, Nb, Pd, Si, Sb, Sr, Se, Ru, Rh, Ta, Te, Ti, W, V, Y, Zr and Zn.
[0015] A second aspect of the present invention provides a method for preparing a positive electrode active material, comprising the following preparation steps: (1) Preparing precursors of cathode active materials with different particle sizes; (2) sintering the obtained precursors of the positive electrode active materials with different particle sizes with lithium sources to prepare positive electrode active materials with three or more particle sizes; (3) Three or more positive electrode active materials with different particle sizes are mixed in a dry environment according to a certain mass ratio to obtain a positive electrode active material.
[0016] A third aspect of the present invention provides a positive electrode sheet, comprising a current collector and a positive electrode active material layer coated on at least one side of the current collector, wherein the positive electrode active material layer comprises a conductive agent, an auxiliary agent and the positive electrode active material described above, or a positive electrode active material prepared by the method for preparing the positive electrode active material described above.
[0017] A fourth aspect of the present invention provides a battery, comprising the positive electrode sheet as described above.
[0018] According to the positive electrode active material provided by the present invention, three or more particles of different particle sizes are used to form the positive electrode active material, and the positive electrode active material includes large particles, medium particles and small particles, wherein the large particles are polycrystalline, and the particles and small particles are polycrystalline or single crystal, and not all polycrystalline, so that the positive electrode active material has a higher gram capacity, can give full play to the rate performance of the battery, and meet the rapid charge and discharge requirements of the battery. The large-particle polycrystalline material is used to construct the framework, and the medium and small particles are used to fill the gaps between the large particles, which is more conducive to improving the compaction density of the positive electrode material to obtain a higher energy density. In addition, the grading of multiple components is conducive to further expanding the source of positive electrode active materials, reducing the impact of batch differences on battery performance, and is more suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0020] Figure 1 Schematic diagram of the structure of the positive electrode active material A provided by the present invention; Figure 2 Schematic diagram of the structure of the positive electrode active material B provided by the present invention; Figure 3 Schematic diagram of the structure of the positive electrode active material C provided by the present invention; Figure 4 is a schematic diagram of the structure of the positive electrode active material provided in Comparative Example 1; Figure 5 is a SEM image of the positive electrode active material A provided in Example 1 of the present invention; Figure 6 is an EDS test image of the first polycrystalline particle in the positive electrode active material A provided in Example 1 of the present invention; Figure 7 is an EDS test image of the second polycrystalline particle in the positive electrode active material A provided in Example 1 of the present invention; Figure 8 is an EDS test image of the first single crystal particle in the positive electrode active material A provided in Example 1 of the present invention; Fig. 9 is the XRD diagram of the positive electrode sheet in Example 2 of the present invention; Fig.10 is a SEM image of the positive electrode sheet in Example 2 of the present invention; Fig.11 is a charge and discharge curve diagram of a liquid system battery provided in Example 1 of the present invention; The reference numerals in the drawings of the specification are as follows: 1-first polycrystalline particle; 2-first single crystal particle; 3-second polycrystalline particle; 4-second single crystal particle. DETAILED DESCRIPTION
[0021] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0023] A first aspect of the present invention provides a positive electrode active material, comprising at least one of a first polycrystalline particle 1, a first single crystal particle 2, a second polycrystalline particle 3, and a second single crystal particle 4; The particle size of the second polycrystalline particle 3 is 0.10 to 0.99 of the particle size of the first polycrystalline particle 1; The particle size of the second single crystal particles 4 is 0.10 to 0.99 of the particle size of the first single crystal particles 2 .
[0024] The present invention proposes a technical solution for combining three or more particles of different particle sizes. The positive electrode active material includes at least one of a first polycrystalline particle 1, a first single crystal particle 2, a second polycrystalline particle 3, and a second single crystal particle 4. While utilizing the excellent cycle performance of large polycrystalline particles and single crystal particles, introducing single crystals with smaller particle sizes can improve the capacity and rate performance of the battery.
[0025] The present invention uses three or more particles of different particle sizes to form the positive electrode active material, so that the positive electrode active material has a higher gram capacity, can give full play to the rate performance of the battery, and meet the rapid charging and discharging requirements of the battery. The large first polycrystalline particles 1 are used to build the framework, the medium first single crystal particles 2 and the small second single crystal particles 4 are used to fill the gaps between the large particles, which is more conducive to improving the compaction density of the positive electrode material to obtain a higher energy density. In addition, the grading of multiple components is conducive to further expanding the source of positive electrode active materials, reducing the impact of batch differences on battery performance, and is more suitable for industrial production.
[0026] In one embodiment, the particle size of the first polycrystalline particle 1 is 8-20 μm; the particle size of the first single crystal particle 2 is 2-6.5 μm.
[0027] Specifically, the particle size of the first polycrystalline particle 1 is any point value of 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm, or a range value consisting of any two point values; in a preferred embodiment, the particle size of the first polycrystalline particle 1 is 12-16μm; Specifically, the particle size of the first single crystal particle 2 is any point value of 2 μm, 2.5 μm, 3 μm, 3.2 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm or 6.5 μm, or a range value consisting of any two point values; in a preferred embodiment, the particle size of the first single crystal particle 2 is 3-5 μm; Specifically, the particle size of the second polycrystalline particles 3 is any point value among 0.8μm, 1.35μm, 2μm, 2.75μm, 3.6μm, 4.55μm, 5.6μm, 6.75μm, 8μm, 9.35μm, 10.8μm, 12.35μm, 14μm, 15.3μm, 16.2μm, 18.05μm or 19.8μm, or a range value consisting of any two point values.
[0028] Specifically, the particle size of the second single crystal particle 4 is any point value among 0.2μm, 0.38μm, 0.6μm, 0.88μm, 1.2μm, 1.58μm, 2.0μm, 2.48μm, 3.0μm, 3.58μm, 4.2μm, 4.88μm, 5.53μm, 6.18μm or 6.44μm, or a range value consisting of any two point values.
[0029] In a preferred embodiment, the particle size of the second polycrystalline particle 3 is 0.35-0.95 of the particle size of the first polycrystalline particle 1 .
[0030] Furthermore, the particle size of the second polycrystalline particles 3 is smaller than that of the first polycrystalline particles 1; thereby, the capacity and rate performance can be improved, and the compaction density of the material is improved under the particle grading, which is more conducive to the performance of its long cycle performance, thereby bringing excellent overall battery performance.
[0031] In a preferred embodiment, the particle size of the second single crystal particles 4 is 0.7-0.9 of the particle size of the first single crystal particles 2 .
[0032] Furthermore, the particle size of the second single crystal particle 4 is smaller than that of the first single crystal particle 2; thereby, the capacity and rate performance can be improved, and the compaction density of the material is improved under the particle grading, which is more conducive to the performance of its long cycle performance, thereby bringing excellent overall battery performance.
[0033] like Figure 1 As shown, in one embodiment, the positive electrode active material includes a positive electrode active material A, the positive electrode active material A includes a first polycrystalline particle 1, a second polycrystalline particle 3 and a first single crystal particle 2, the mass of the first polycrystalline particle 1 is m1, the mass of the second polycrystalline particle 3 is m2, the mass of the first single crystal particle 2 is m3, and m1, m2, and m3 satisfy the relationship: 70%≤(m1+m2) / (m1+m2+m3)≤90%; 1%≤m2 / (m1+m2)≤99%.
[0034] Specifically, the ratio of (m1+m2) / (m1+m2+m3) is any point value of 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89% or 90%, or a range of any two point values; in a preferred embodiment, m1, m2, and m3 satisfy the relationship: 75%≤(m1+m2) / (m1+m2+m3)≤85%; Specifically, the ratio of m2 / (m1+m2) is any point value of 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 99%, or a range of any two point values; in a preferred embodiment, m1 and m2 satisfy the relationship: 40%≤m2 / (m1+m2)≤60%; When m1, m2, and m3 satisfy the relationship: 70%≤(m1+m2) / (m1+m2+m3)≤90%; 1%≤m2 / (m1+m2)≤99%, the capacity and rate performance can be improved, and the compaction density of the material is improved under the particle grading, which is more conducive to the long cycle performance, thereby bringing excellent overall battery performance.
[0035] like Figure 1 As shown, in one embodiment, the positive electrode active material includes a positive electrode active material B, and the positive electrode active material B includes a first polycrystalline particle 1, a first single crystal particle 2, and a second single crystal particle 4. The mass of the first polycrystalline particle 1 is m4, the mass of the first single crystal particle 2 is m5, and the mass of the second single crystal particle 4 is m6. m4, m5, and m6 satisfy the relationship: 70%≤m4 / (m4+m5+m6)≤90%; 1%≤m6 / (m5+m6)≤99%.
[0036] Specifically, the ratio of m4 / (m4+m5+m6) is any one of 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89% or 90%, or a range consisting of any two of the values; in a preferred embodiment, m4, m5, and m6 satisfy the relationship: 75%≤m4 / (m4+m5+m6)≤85%; Specifically, the ratio of m6 / (m5+m6) is any point value of 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 99%, or a range of any two point values; in a preferred embodiment, m4 and m5 satisfy the relationship: 40%≤m6 / (m5+m6)≤60%; When m4, m5, and m6 satisfy the relationship: 70%≤m4 / (m4+m5+m6)≤90%; 1%≤m6 / (m5+m6)≤99%, the capacity and rate performance can be improved, and the compaction density of the material is improved under the particle grading, which is more conducive to the long cycle performance, thereby bringing excellent overall battery performance.
[0037] like Figure 3 As shown, in one embodiment, the positive electrode active material includes a positive electrode active material C, the positive electrode active material C includes a first polycrystalline particle 1, a first single crystal particle 2, a second single crystal particle 4 and a second polycrystalline particle 3, the mass of the first polycrystalline particle 1 is m7, the mass of the second polycrystalline particle 3 is m8, the mass of the first single crystal particle 2 is m9, the mass of the second single crystal particle 4 is m10, and m7, m8, m9 and m10 satisfy the relationship: 70%≤(m7+m8) / (m7+m8+m9+m10)≤90%; 1%≤m7 / (m7+m8)≤99%; 1%≤m9 / (m9+m10)≤99%.
[0038] Specifically, the ratio of (m7+m8) / (m7+m8+m9+m10) is any one of 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89% or 90%, or a range of any two of the values; in a preferred embodiment, m4, m5, and m6 satisfy the relationship: 75%≤(m7+m8) / (m7+m8+m9+m10)≤85%; Specifically, the ratio of m7 / (m7+m8) is any point value of 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 99%, or a range of any two point values; in a preferred embodiment, m4 and m5 satisfy the relationship: 40%≤m7 / (m7+m8)≤60%; Specifically, the ratio of m9 / (m9+m10) is any point value of 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 99%, or a range of any two point values; in a preferred embodiment, m4 and m5 satisfy the relationship: 40%≤m9 / (m9+m10)≤60%; When m7, m8, m9 and m10 satisfy the relationship: 70%≤(m7+m8) / (m7+m8+m9+m10)≤90%; 1%≤m7 / (m7+m8)≤99%; 1%≤m9 / (m9+m10)≤99%, the capacity and rate performance can be improved, and the compaction density of the material is improved under the particle grading, which is more conducive to the long cycle performance, thereby bringing excellent comprehensive battery performance.
[0039] In one embodiment, the positive electrode active material also includes supplementary particles, the particle size of the supplementary particles is different from the particle size of the first polycrystalline particles 1, the first single crystal particles 2, the second polycrystalline particles 3 and the second single crystal particles 4. Taking the total mass of the positive electrode active material as 100%, the supplementary particles account for 1%-30% of the mass of the positive electrode active material.
[0040] Specifically, the supplementary particles can be one or more of polycrystalline particles and single crystal particles, and the supplementary particles account for any point value of 1%, 5%, 10%, 15%, 20%, 25% or 30% of the mass of the positive electrode active material or a range value consisting of any two point values; in a preferred embodiment, the supplementary particles account for 5%-20% of the mass of the positive electrode active material.
[0041] When the mass percentage of supplementary particles in the positive electrode active material is 1-30%, the capacity and rate performance can be improved, and the material compaction density is increased under the particle grading, which is more conducive to its long cycle performance, thus bringing excellent battery comprehensive performance. When the mass percentage of supplementary particles in the positive electrode active material is greater than 30%, the particle grading effect will be deteriorated, and the mismatch between the proportions of the sizes will lead to poor rate and cycle performance.
[0042] In one embodiment, the first polycrystalline particles 1, the first single crystal particles 2, the second polycrystalline particles 3, the second single crystal particles 4 and the supplementary particles are all ternary positive electrode active materials, and the ternary positive electrode active materials include one or more of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide.
[0043] The selection of ternary positive electrode active materials has higher specific capacity and specific energy, allowing the battery to store more energy; In a preferred embodiment, the ternary positive electrode active material includes lithium nickel cobalt manganese oxide.
[0044] In one embodiment, the chemical formula of lithium nickel cobalt manganese oxide is Li 1+a Ni x Co y Mn z O 2 , where a, x, y, and z satisfy the relationship: x+y+z=1; -0.1 <a<0.2。
[0045] Specifically, the value range of a is any point value among -0.09, -0.08, -0.07, -0.06, -0.05, -0.04, -0.03, -0.02, -0.01, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18 or 0.19, or a range of values consisting of any two point values; in a preferred embodiment, the value range of a is -0.05 to 0.15; Specifically, x, y, and z are all positive numbers; wherein the value range of x is 0.33≤x<1.00; specifically, the value range of x is any point value among 0.33, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, or 0.99, or a range of values consisting of any two point values; in a preferred embodiment, the value range of x is 0.5≤x≤0.98; The value range of y is 0.0≤y≤0.5; specifically, the value range of y is any point value or any range of two point values among 0.0, 0.1, 0.2, 0.3, 0.4 or 0.5; in a preferred embodiment, the value range of y is 0.01≤y≤0.3; The value range of z is 0.0≤z≤0.5; specifically, the value range of z is any point value among 0.0, 0.1, 0.2, 0.3, 0.4 or 0.5, or a range value consisting of any two point values; in a preferred embodiment, the value range of z is 0.01≤z≤0.3.
[0046] In one embodiment, the positive electrode active material also includes a doping element and a coating element. The doping element is mixed with the ternary positive electrode active material and doped inside the ternary positive electrode active material, and the coating element is coated on the outside of the ternary positive electrode active material, so that the synthesized positive electrode active material achieves a better balance in capacity and safety.
[0047] Taking the total mass of the positive electrode active material as 100%, the mass fraction of the ternary positive electrode active material in the positive electrode active material is 90-100%; the mass fraction of the doping element in the positive electrode active material is 0.01-5.0%; and the mass fraction of the coating element in the positive electrode active material is 0.01-5.0%.
[0048] In one embodiment, the element doping includes one or more of Al, B, Ba, Bi, Ca, Cr, Ce, Co, Er, Ga, Ge, Ho, K, La, Mg, Mo, Na, Nb, Pd, Si, Sb, Sr, Se, Ru, Rh, Ta, Te, Ti, W, V, Y, Zr and Zn. The above elements are doped inside the ternary positive electrode active material, and the material has a low-valent ion supporting Li layer and a high-valent cation stabilizing transition metal layer, thereby achieving a highly lattice rivet stabilization effect.
[0049] In one embodiment, the coating elements include one or more of Al, B, Ba, Bi, Ca, Cr, Ce, Co, Er, Ga, Ge, Ho, K, La, Mg, Mo, Na, Nb, Pd, Si, Sb, Sr, Se, Ru, Rh, Ta, Te, Ti, W, V, Y, Zr and Zn. The above elements are coated on the outside of the ternary positive electrode active material, and the material is uniformly coated with mechanical toughness, conductivity, ion conductivity and chemical stability, so as to prevent external material erosion and internal mechanical failure.
[0050] A second aspect of the present invention provides a method for preparing a positive electrode active material, comprising the following preparation steps: (1) Preparing precursors of cathode active materials with different particle sizes; (2) sintering the obtained precursors of the positive electrode active materials with different particle sizes with lithium sources to prepare positive electrode active materials with three or more particle sizes; (3) Three or more positive electrode active materials with different particle sizes are mixed in a dry environment according to a certain mass ratio to obtain a positive electrode active material.
[0051] Specifically, in step (1), a coprecipitation method is used to prepare nickel-cobalt-manganese hydroxide or nickel-cobalt-aluminum hydroxide of different particle sizes as a precursor; In step (2), the obtained nickel-cobalt-manganese hydroxide precursors of different particle sizes are mixed with lithium sources at a molar ratio of Li / (Ni+Co+Mn)=0.9-1.1, and sintered at 600-1000°C for 3-48h to prepare positive electrode active materials of three or more particle sizes; or, The obtained nickel-cobalt-aluminum hydroxide precursors of different particle sizes are mixed with lithium sources at a molar ratio of Li / (Ni+Co+Al)=0.9-1.1, and sintered at 600-1000°C for 3-48h to prepare positive electrode active materials of three or more particle sizes; The third aspect of the present invention provides a positive electrode sheet, including a current collector and a positive electrode active material layer coated on at least one side of the current collector, the positive electrode active material layer including a conductive agent, an auxiliary agent and a positive electrode active material prepared by the above-mentioned positive electrode active material, or by the above-mentioned method for preparing the positive electrode active material.
[0052] In some embodiments, the conductive agent includes one or more of graphite, hard carbon, soft carbon, carbon nanotubes, graphene, porous carbon, superconducting carbon black (SuperP), acetylene black (AcetyleneBlack), and furnace black (FurnaceBlack).
[0053] In some embodiments, the additive includes one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), silicone rubber, styrene-butadiene rubber (SBR), hydrogenated nitrile rubber (HNBR), boronated polyethylene glycol, cellulose, cellulose ester, cellulose ether, nitrocellulose, carboxyalkyl cellulose, cellulose salt, sodium carboxymethyl cellulose and cellulose salt derivatives, polyacrylic acid (PAA), polyamide (PAI), polyvinyl alcohol (PVA), polyethyleneimine (PEI), and polyimide (PI).
[0054] In some embodiments, the mass percentage of each component in the positive electrode active material layer is: 80-99 wt % of positive electrode active material, 0.5-10 wt % of conductive agent, and 0.5-10 wt % of auxiliary agent.
[0055] In some embodiments, the positive electrode active material layer also contains 0.1 to 30 wt% of a solid electrolyte, and the ratio of the other components remains unchanged. Solid electrolytes include, but are not limited to: one or more of NASICON solid electrolytes, LISICON solid electrolytes, garnet solid electrolytes, perovskite solid electrolytes, antiperovskite solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, and polymer electrolytes. Polymer electrolytes include polymers and lithium salts; polymers include, but are not limited to PEO, PVDF, PVDF-HFP, PMMA, PAN; lithium salts include, but are not limited to LiPF 6 , LiTFSI, LiFSI, LiDFOB.
[0056] When the mass proportion of the positive electrode active material in the positive electrode active material layer is within the above range, the positive electrode plate can have a higher gram capacity, can give full play to the rate performance of the battery, and meet the fast charging and discharging requirements of the battery.
[0057] In some embodiments, the positive electrode current collector is selected from a metal material that can conduct electrons. Preferably, the positive electrode current collector includes one or more of copper, nickel, tin, copper, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.
[0058] There are two methods for preparing positive electrode sheets. Method 1: Wet preparation S1: Mixing the positive electrode active material, the conductive agent and the auxiliary agent in a preset ratio to form a positive electrode slurry; S2: coating the obtained positive electrode slurry on the positive electrode current collector according to a certain loading amount; S3: drying the positive electrode current collector coated with the positive electrode slurry, and then rolling it to obtain a positive electrode sheet.
[0059] Method 2: Fibrillation preparation S1: mixing the positive electrode active material, the conductive agent and the auxiliary agent in a preset ratio, applying shear force to the mixed powder to fiberize the auxiliary agent to obtain a blank; S2: extruding or rolling the blank into a self-supporting film; S3: Load the self-supporting film onto the positive electrode current collector rolling between two rollers, and roll-press to form a positive electrode sheet.
[0060] A fourth aspect of the present invention provides a battery, comprising the positive electrode sheet as described above.
[0061] The battery of the present application includes a negative electrode sheet, a separator and an electrolyte in addition to the above-mentioned positive electrode sheet; In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one side or both sides of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a conductive agent, a binder, and a thickener.
[0062] In one embodiment, the negative electrode active material includes but is not limited to metal lithium Li or metal lithium alloy Li-M, artificial graphite, natural graphite, modified graphite, fast-charged graphite, soft carbon, hard carbon, gas phase silicon carbon, ground silicon carbon, SiO x , pre-lithiated silicon oxide, pre-magnesiumized silicon oxide or more; wherein the metal lithium alloy Li-M can be an alloy formed by metal lithium and one or more of gold, indium, magnesium, zinc, chromium, nickel, molybdenum, tungsten, vanadium, titanium, niobium, zirconium, cobalt, manganese, aluminum, copper, boron, silver, tin, silicon, carbon, phosphorus and the like, wherein the mass content of metal lithium is 1-99%.
[0063] In some embodiments, the negative electrode conductive agent includes one or more of super-P, VGCF, and CNT.
[0064] In some embodiments, the negative electrode binder includes one or more of PVDF, SBR, NBR, BR, and CMC.
[0065] In some embodiments, the thickening agent includes one or more of sodium alginate, sodium carboxymethyl cellulose, and carboxymethyl chitosan.
[0066] In some embodiments, the mass percentage of each component in the negative electrode active material layer is: 80-100 wt % of the negative electrode active material, 0-10 wt % of the conductive agent, and 0-10 wt % of the binder.
[0067] The negative electrode current collector is selected from metal materials that can conduct electrons. Preferably, the negative electrode current collector includes one or more of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the negative electrode current collector is selected from copper foil.
[0068] The negative electrode sheet can be prepared according to conventional methods in the art. For example, the negative electrode active material layer is usually prepared by coating a negative electrode slurry made of a negative electrode active material, a negative electrode conductive agent, a negative electrode binder and any other components on a negative electrode current collector, followed by drying and cold pressing. The solvent can be an aqueous solvent, but is not limited thereto.
[0069] The diaphragm includes a base film, which is one or more of a PE diaphragm, a PP diaphragm, a non-woven fabric diaphragm, and a PI diaphragm.
[0070] In some embodiments, at least one side of the base film contains a coating; the coating includes: an oxide solid electrolyte, an alkaline oxide, and a polymer adhesive; the oxide solid electrolyte and the alkaline oxide are dispersed in the polymer adhesive; the alkaline oxide includes at least one of aluminum oxide and boehmite. The oxide solid electrolyte includes: at least one of a NASICON solid electrolyte, a garnet solid electrolyte, and a perovskite solid electrolyte.
[0071] Electrolytes: Electrolytes include but are not limited to: conventional electrolytes, including organic solvents, lithium salts and additives, solvents including but not limited to PC, EC, DMC, EMC, DEC and DME; gel electrolytes, including polymer matrix, plasticizing solvent, lithium salt; in-situ polymerized electrolytes, including polymer monomers, lithium salts, solvents, initiators; eutectic electrolytes, including small molecule polar matrix and lithium salts; ionic liquid electrolytes, including ionic liquids and lithium salts. Lithium salts include but are not limited to lithium hexafluorophosphate LiPF 6 、Lithium hexafluoroarsenate LiAsF 6 、Lithium tetrafluoroborate LiBF 4 、Lithium hexafluoroantimonate LiSbF 6 , Lithium bis(trifluoromethanesulfonimide) LiTFSI or LiN(SO 2 CF 2 ) 2 、Lithium trifluoromethanesulfonate LiCF 3 SO 3 、LiFSI or LiN(SO 2 CF 3 ) 2 、Lithium Perchlorate LiClO 4 , lithium iodide LiI, lithium magnesium bis(fluorosulfonyl)imidate Li 2 Mg(N(SO 2 CF 3 ) 2 )2 .
[0072] Electrolytes include liquid electrolytes, semi-solid electrolytes and all-solid electrolytes; Liquid electrolytes are applied to one or more of soft-pack batteries, cylindrical batteries or square-shell batteries; semi-solid electrolytes are applied to one or more of soft-pack batteries, cylindrical batteries or square-shell batteries; all-solid electrolytes are applied to one or more of soft-pack batteries, cylindrical batteries or square-shell batteries.
[0073] Solid electrolytes include but are not limited to: one or more of NASICON solid electrolytes, LISICON solid electrolytes, garnet solid electrolytes, perovskite solid electrolytes, antiperovskite solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, and polymer electrolytes. Polymer electrolytes include polymers and lithium salts; polymers include but are not limited to PEO, PVDF, PVDF-HFP, PMMA, and PAN; lithium salts include but are not limited to LiPF 6 , LiTFSI, LiFSI, LiDFOB.
[0074] The beneficial effects of the present invention are further illustrated below in conjunction with embodiments.
[0075] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with examples. However, it should be understood that the examples of the present invention are only for explaining the present invention, not for limiting the present invention, and the examples of the present invention are not limited to the examples given in the specification. The specific experimental conditions or operating conditions not specified in the examples are prepared under conventional conditions, or prepared under the conditions recommended by the material supplier.
[0076] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0077] In the following examples, the reagents, materials and instruments used, unless otherwise specified, can be purchased commercially or obtained by synthetic methods known in the art.
[0078] Table 1 Design of positive electrode active materials, negative electrode active materials and electrolytes of Examples 1-7 and Comparative Examples 1-7; Note: The first polycrystalline particle is A1; the second polycrystalline particle is A2; the first single crystal particle is B1; the second single crystal particle is B2; Example 1 Preparation of positive electrode active materials: The large particles (12 μm) of nickel cobalt manganese hydroxide precursor (Ni 0.9 0Co 0.05 Mn 0.05 (OH) 2 and lithium hydroxide monohydrate, dopant aluminum oxide (Al 2 O 3 , Al doping amount 2000ppm), according to Li / Me=1.03, sintered at 730℃ for 15h in oxygen atmosphere to obtain a sintered product; the sintered product was crushed, washed with water, and dried, and the dried product was mixed with boron oxide (Nb 2 O 5 , Nb coating amount 1000ppm) was sintered at 250°C for 8h in an oxygen atmosphere, and passed through a 325-mesh sieve to obtain the first polycrystalline particles with a particle size of 11.8μm.
[0079] The medium-sized (8 μm) nickel-cobalt-manganese hydroxide precursor (Ni 0.89 Co 0.06 Mn 0.05 (OH) 2 and lithium hydroxide monohydrate, dopant zirconium oxide (ZrO 2 , Zr doping amount 3000ppm), according to Li / Me=1.04, sintered at 720℃ for 13h in oxygen atmosphere to obtain a calcined product; the calcined product was crushed, washed with water, and dried, and the dried product was mixed with alumina (WO 3 The second polycrystalline particles were sintered at 450°C for 8 hours in an oxygen atmosphere with a coating amount of 2000 ppm and passed through a 325 mesh sieve to obtain the second polycrystalline particles with a particle size of 7.5 μm.
[0080] Small particles (3 μm) of nickel cobalt manganese hydroxide precursor (Ni 0.90 Co 0.05 Mn 0.05 (OH) 2 and lithium hydroxide monohydrate, dopant strontium oxide (SrO, Sr doping amount 1000ppm), according to Li / Me=1.05, sintered at 900℃ for 15h in an oxygen atmosphere to obtain a calcined product; the calcined product was crushed and dried, and the dried product was mixed with zirconium oxide (Al 2 O3 , Al coating amount 1500ppm) was sintered at 550℃ for 8h in oxygen atmosphere, and passed through a 325 mesh sieve to obtain the first single crystal particle. Its primary particle size is 2.0μm and the particle diameter is 3.5μm.
[0081] like Figure 1 As shown, the first polycrystalline particles, the second polycrystalline particles and the first single crystal particles prepared above are weighed and mixed evenly in a mass ratio of 7:1:2 to obtain a positive electrode active material.
[0082] Preparation of positive electrode: The positive electrode active material, conductive agent SP, and binder PVDF obtained above are mixed in a mass ratio of 92:4:4. They are fully stirred and mixed in NMP solvent to form a uniform positive electrode slurry. The slurry is coated on at least one side of the positive electrode current collector aluminum foil, and after drying, rolling, die-cutting and other processes, a positive electrode sheet that meets the requirements is obtained.
[0083] Preparation of negative electrode: The negative electrode active material graphite, conductive agent SP, binder CMC, SBR are mixed in a mass ratio of 96:2:1:1. The mixture is fully stirred and mixed in a deionized water solvent to form a uniform negative electrode slurry. The slurry is applied to at least one side of the negative electrode current collector copper foil, and after drying, rolling, die-cutting and other processes, a negative electrode sheet that meets the requirements is obtained.
[0084] Preparation of diaphragm: PE porous polymer film is used as the diaphragm; Preparation of electrolyte: Lithium salt LiPF 6 Dissolved in organic solvent EC-DMC (1:1 volume ratio) with a concentration of 1M to obtain a liquid electrolyte.
[0085] Preparation of the battery: The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, and the separator is placed in the middle of the positive and negative electrodes to play an isolating role. Then, the positive electrode sheet, the separator and one end of the negative electrode sheet are wound around the electrolyte separator to form a roll core, and then the rolled roll core is placed in the aluminum-plastic film bag formed by punching and forming the shell, and the prepared electrolyte is respectively injected into the baked and dried battery cells. After vacuum packaging, standing, formation and other processes, a battery with a capacity of 1Ah is obtained.
[0086] Example 2 Example 2 is used to illustrate the positive electrode active material, positive electrode plate and battery disclosed in the present invention, and includes most of the operation steps in Example 1, except that: Preparation of positive electrode active materials: The large particles (12 μm) of hydroxide precursor (Ni 0.90 Co0.05 Mn 0.05 (OH) 2 and lithium hydroxide monohydrate, dopant aluminum oxide (Al 2 O 3 , Al doping amount 2000ppm), according to Li / Me=1.03, sintered at 730℃ for 15h in oxygen atmosphere to obtain a sintered product; the sintered product was crushed, washed with water, and dried, and the dried product was mixed with boron oxide (B 2 O 3 , B coating amount 1000ppm) was sintered at 350°C for 8h in an oxygen atmosphere, and passed through a 325-mesh sieve to obtain the first polycrystalline particles with a particle size of 11.9μm.
[0087] Small particles (3 μm) of hydroxide precursor (Ni 0.80 Co 0.05 Mn 0.15 (OH) 2 and lithium hydroxide monohydrate, dopant strontium carbonate (SrCO 3 , Sr doping amount 1000ppm), according to Li / Me=1.05, sintered at 930℃ for 15h in an oxygen atmosphere to obtain a calcined product; the calcined product was crushed and dried, and the dried product was mixed with zirconium oxide (ZrO 2 , Zr coating amount 1500ppm) was sintered at 550℃ for 8h in oxygen atmosphere, and passed through a 325 mesh sieve to obtain the first single crystal particle. Its primary particle size is 2.4μm and the particle diameter is 3.8μm.
[0088] Small particles (2.3 μm) of hydroxide precursor (Ni 0.85 Co 0.10 Mn 0.05 (OH) 2 and lithium hydroxide monohydrate, dopant boric acid (H 3 BO 3 , B doping amount 1000ppm), according to Li / Me=1.04, sintered at 880℃ for 15h in oxygen atmosphere to obtain a sintered product; the sintered product was crushed and dried, and the dried product was sintered with magnesium oxide (MgO, Mg coating amount 1000ppm) at 550℃ for 8h in oxygen atmosphere, and passed through a 325 mesh sieve to obtain a second single crystal particle. Its primary particle size is 1.6μm and the particle size is 2.5μm.
[0089] like Figure 2 As shown, the first polycrystalline particles, the first single crystal particles and the second single crystal particles prepared above are weighed and mixed evenly in a mass ratio of 7:2:1 to obtain a positive electrode active material.
[0090] Preparation of positive electrode: The positive electrode active material, conductive agent SP, binder PVDF, and solid electrolyte LLZTO obtained above are mixed in a mass ratio of 90:4:4:2. The mixture is fully stirred and mixed in NMP solvent to form a uniform positive electrode slurry. The slurry is coated on at least one side of the positive electrode current collector aluminum foil, and a positive electrode sheet that meets the requirements is obtained after drying, rolling, die-cutting and other processes.
[0091] Preparation of negative electrode: Pure Li metal is used as the negative electrode, and after processes such as die-cutting, the negative electrode sheet that meets the requirements is obtained.
[0092] Preparation of electrolyte: The organic polymer PEO, lithium salt LiTFSI and additive LLTO were mixed in an organic solvent DMF at a mass ratio of 6:4:1, and a solid electrolyte membrane was obtained after coating and drying. The lithium salt LiFSI was dissolved in an organic solvent DME-TTE (22:78 volume ratio) at a concentration of 1.54 M to obtain a liquid electrolyte.
[0093] Preparation of the battery: The positive electrode sheet, solid electrolyte membrane and negative electrode sheet are stacked in order, so that the solid electrolyte membrane is located between the positive and negative electrodes to isolate and conduct lithium ions. Then the positive electrode sheet, separator and negative electrode sheet are stacked in order and placed in an aluminum-plastic film bag. The prepared liquid electrolyte is injected into the baked and dried battery cell. After vacuum packaging, standing, formation and other processes, a battery with a capacity of 1Ah is obtained.
[0094] Example 3 Example 3 is used to illustrate the positive electrode active material, positive electrode sheet and battery disclosed in the present invention, including most of the operating steps in Example 1 and Example 2, and the difference is that: like Figure 3 As shown, the first polycrystalline particles, the second polycrystalline particles, the first single crystal particles prepared in Example 1 and the second single crystal particles prepared in Example 2 are weighed and mixed uniformly in a mass ratio of 75:5:12:8 to obtain a positive electrode active material.
[0095] Preparation of positive electrode: The positive electrode active material, conductive agent SP, binder PVDF, and solid electrolyte LLZTO obtained above are mixed in a mass ratio of 80:4:4:12. They are fully stirred and mixed in NMP solvent to form a uniform positive electrode slurry. The slurry is coated on at least one side of the positive electrode current collector aluminum foil, and after drying, rolling, die-cutting and other processes, a positive electrode sheet that meets the requirements is obtained.
[0096] Preparation of negative electrode: The negative electrode active material silicon carbon, the conductive agent SP, and the binder PAA are mixed in a mass ratio of 93: 3: 4. The mixture is fully stirred and mixed in a deionized water solvent to form a uniform negative electrode slurry. The slurry is coated on at least one side of the negative electrode current collector copper foil, and after drying, rolling, die cutting and other processes, a negative electrode sheet that meets the requirements is obtained.
[0097] Preparation of electrolyte: The organic polymer PVDF, the lithium salt LiTFSI and the additive LLZTO are mixed in an organic solvent DMF at a mass ratio of 6:4:1, and a solid electrolyte membrane is obtained after coating and drying.
[0098] Preparation of the battery: The positive electrode sheet, solid electrolyte membrane and negative electrode sheet are stacked in order, so that the solid electrolyte membrane is in the middle of the positive and negative electrodes to isolate and conduct lithium ions. Then the positive electrode sheet, separator and negative electrode sheet are stacked in order and placed in an aluminum-plastic film bag. The battery cell after baking and drying is vacuum packaged, left to stand, formed and other processes to obtain a battery with a capacity of 1Ah.
[0099] Embodiment 4-7 Examples 4-7 are used to illustrate the positive electrode active material, positive electrode sheet and battery disclosed in the present invention, including most of the operating steps in Example 1, except that: Various components and contents of the positive electrode active materials shown in Table 1 were used.
[0100] Comparative Examples 1-7 Comparative Examples 1-7 are used to illustrate the positive electrode active material, positive electrode sheet and battery disclosed in the present invention, and include most of the operating steps in Example 1, except that: Various components and contents of the positive electrode active materials shown in Table 1 were used.
[0101] Test method: The liquid battery, semi-solid battery and solid battery assembled from the positive electrode materials obtained in Examples 1-7 and Comparative Examples 1-7 were subjected to charge and discharge tests and cycle tests. If no specific technology or conditions are specified, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0102] 1. First discharge specific capacity test The method includes: performing charge and discharge cycles at a set current density at room temperature using a constant current and constant voltage charge and discharge instrument (such as Battery Testing System). The positive electrode active material is made into a standard battery button or soft pack battery, and the counter electrode is lithium metal.
[0103] Test steps: 1. Charge to the set cut-off voltage of 4.3V at the set current density (0.1C).
[0104] 2. Discharge at the same current density (0.1C) until the set discharge cut-off voltage of 2.8V is reached.
[0105] 3. Record the specific capacity of the first discharge in mAh / g.
[0106] 2. First cycle coulomb efficiency test Including: At room temperature, a constant current and constant voltage charge and discharge instrument is also used to measure the amount of electricity passing through the battery during the first charge and discharge process during the test.
[0107] Test steps: 1. Charge to the set voltage and record the total charge (Q_charge).
[0108] 2. Discharge to the set cut-off voltage and record the total discharged power (Q_discharge).
[0109] 3. Calculate the first-cycle coulombic efficiency: Coulombic efficiency = (Q_discharge / Q_charge) × 100%.
[0110] 3.100-week capacity retention test The method includes: performing 100 charge and discharge cycles on the positive electrode active material at room temperature under the same current density and voltage window.
[0111] Test steps: 1. Perform 100 charge and discharge cycles on the battery, and periodically record the discharge capacity each time; 2. Calculate the capacity retention after 100 cycles: Capacity retention rate = (discharge capacity at the 100th week / first discharge capacity) × 100%.
[0112] Test results: See Table 2.
[0113] Table 2 like Figure 4 As shown, it is a SEM image of the positive electrode active material A provided in Comparative Example 1 of the present invention. It can be seen from the figure that two polycrystalline particles with larger particle sizes (first polycrystalline particles or second polycrystalline particles) are mixed with the first single crystal particles. Among them, the particle size of A1 is 11.8μm, the particle size of B1 is 7.5μm, and the primary particle size of C1 is 2.0μm.
[0114] like Figure 5 , which is a SEM image of the positive electrode active material A provided in Example 1 of the present invention; like Figure 6 As shown, it is an EDS test image of the first polycrystalline particle in Example 1 of the present invention, indicating that it is coated with Nb element; like Figure 7 As shown, it is an EDS test image of the second polycrystalline particle in Example 1 of the present invention, indicating that it is coated with W element; like Figure 8 As shown, the EDS test image of the first single crystal particle in Example 1 of the present invention shows that it is coated with Al element.
[0115] like Fig. 9 , which is the XRD diagram of the positive electrode sheet in Inventive Example 2; like Fig.10 , which is a SEM image of the positive electrode sheet in Example 2 of the present invention; like Fig.11 As shown, it is a charge and discharge curve diagram of the liquid system battery provided in Example 1 of the present invention; It can be seen from Table 2 that when the positive electrode active materials prepared in Examples 1 to 7 include three or more particles of different particle sizes, they can be widely used in liquid batteries, semi-solid batteries and solid-state batteries, and can improve the capacity and rate performance of the battery.
[0116] By comparing Examples 1-3 with Comparative Examples 1-3 and 6-7, it can be seen that when the positive electrode active material contains at least one of the first polycrystalline particles, the first single crystal particles, the second polycrystalline particles and the second single crystal particles, the capacity and cycle performance of the battery can be effectively improved. When there are only two particles with different particle sizes or a single particle, the capacity and cycle performance of the battery cannot be effectively improved.
[0117] By comparing Example 1 with Comparative Examples 4-5, it can be seen that when the proportion of polycrystalline particles in the positive electrode active material is too high or too low, the capacity and cycle performance of the battery cannot be effectively improved.
[0118] In summary, the present application forms the positive electrode active material of the present application by combining three or more ternary positive electrode active material particles of different particle sizes, and the positive electrode active material includes at least one of a first polycrystalline particle, a first single crystal particle, a second polycrystalline particle, and a second single crystal particle. While utilizing the excellent cycle performance of large polycrystalline particles and single crystal particles, the introduction of single crystals and / or polycrystalline particles with smaller particle sizes can improve the capacity and rate performance of the battery. The present invention uses three or more particles of different particle sizes to form the positive electrode active material, so that the positive electrode active material has a higher gram capacity, can give full play to the rate performance of the battery, and meet the rapid charging and discharging requirements of the battery. Large particles are used to construct the framework, and medium particles and small particles are used to fill the gaps between large particles, which is more conducive to increasing the compaction density of the positive electrode material to obtain a higher energy density. In addition, the grading of multiple components is conducive to further expanding the source of positive electrode active materials, reducing the impact of batch differences on battery performance, and is more suitable for industrial production.
[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A positive electrode active material, characterized in that: including at least one of a first polycrystalline particle, a first single crystal particle, a second polycrystalline particle, and a second single crystal particle; The particle size of the second polycrystalline particles is 0.10 to 0.99 of the particle size of the first polycrystalline particles; The particle size of the second single crystal particles is 0.10 to 0.99 of the particle size of the first single crystal particles.
2. The positive electrode active material according to claim 1, characterized in that: The particle size of the first polycrystalline particles is 8-20 μm; the particle size of the first single crystal particles is 2-6.5 μm.
3. The positive electrode active material according to any one of claims 1 to 2, characterized in that: The particle size of the second polycrystalline particles is 0.35 to 0.95 of the particle size of the first polycrystalline particles; the particle size of the second single crystal particles is 0.7 to 0.9 of the particle size of the first single crystal particles.
4. The positive electrode active material according to claim 3, characterized in that: The positive electrode active material includes positive electrode active material A, and the positive electrode active material A includes the first polycrystalline particles, the second polycrystalline particles and the first single crystal particles. The mass of the first polycrystalline particles is m1, the mass of the second polycrystalline particles is m2, and the mass of the first single crystal particles is m3. The m1, m2, and m3 satisfy the relationship: 70%≤(m1+m2) / (m1+m2+m3)≤90%; 1%≤m2 / (m1+m2)≤99%.
5. The positive electrode active material according to claim 3, characterized in that: The positive electrode active material includes positive electrode active material B, and the positive electrode active material B includes the first polycrystalline particles, the first single crystal particles and the second single crystal particles. The mass of the first polycrystalline particles is m4, the mass of the first single crystal particles is m5, and the mass of the second single crystal particles is m6. The m4, m5, and m6 satisfy the relationship: 70%≤m4 / (m4+m5+m6)≤90%; 1%≤m6 / (m5+m6)≤99%.
6. The positive electrode active material according to claim 3, characterized in that: The positive electrode active material includes a positive electrode active material C, and the positive electrode active material C includes the first polycrystalline particles, the first single crystal particles, the second single crystal particles and the second polycrystalline particles, the mass of the first polycrystalline particles is m7, the mass of the second polycrystalline particles is m8, the mass of the first single crystal particles is m9, and the mass of the second single crystal particles is m10, and m7, m8, m9 and m10 satisfy the relationship: 70%≤(m7+m8) / (m7+m8+m9+m10)≤90%; 1%≤m7 / (m7+m8)≤99%; 1%≤m9 / (m9+m10)≤99%.
7. The positive electrode active material according to any one of claims 4 to 6, characterized in that: The positive electrode active material also includes supplementary particles, the particle size of the supplementary particles is different from the particle size of the first polycrystalline particles, the first single crystal particles, the second polycrystalline particles and the second single crystal particles. Taking the total mass of the positive electrode active material as 100%, the supplementary particles account for 1%-30% of the mass of the positive electrode active material.
8. The positive electrode active material according to claim 7, characterized in that: The first polycrystalline particles, the first single crystal particles, the second polycrystalline particles, the second single crystal particles and the supplementary particles are all ternary positive electrode active materials, and the ternary positive electrode active materials include one or more of lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide.
9. The positive electrode active material according to claim 8, characterized in that: The chemical formula of the lithium nickel cobalt manganese oxide is Li1+aNixCoyMnzO2, wherein a, x, y, and z satisfy the relationship: x+y+z=1; -0.1 <a<0.2。 10. The positive electrode active material according to claim 8, characterized in that: The positive electrode active material further includes a doping element and a coating element. The doping element is mixed with the ternary positive electrode active material and doped inside the ternary positive electrode active material, and the coating element is coated outside the ternary positive electrode active material.
11. The positive electrode active material according to claim 10, characterized in that: The element doping includes one or more of Al, B, Ba, Bi, Ca, Cr, Ce, Co, Er, Ga, Ge, Ho, K, La, Mg, Mo, Na, Nb, Pd, Si, Sb, Sr, Se, Ru, Rh, Ta, Te, Ti, W, V, Y, Zr and Zn.
12. The positive electrode active material according to claim 10, characterized in that: The coating elements include one or more of Al, B, Ba, Bi, Ca, Cr, Ce, Co, Er, Ga, Ge, Ho, K, La, Mg, Mo, Na, Nb, Pd, Si, Sb, Sr, Se, Ru, Rh, Ta, Te, Ti, W, V, Y, Zr and Zn.
13. The method for preparing a positive electrode active material according to any one of claims 1 to 12, characterized in that: The method comprises the following preparation steps: (1) Preparing precursors of cathode active materials with different particle sizes; (2) sintering the obtained precursors of the positive electrode active materials with different particle sizes with lithium sources to prepare positive electrode active materials with three or more particle sizes; (3) Three or more positive electrode active materials with different particle sizes are mixed in a dry environment according to a certain mass ratio to obtain a positive electrode active material.
14. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode active material layer coated on at least one side of the current collector, wherein the positive electrode active material layer comprises a conductive agent, an auxiliary agent and the positive electrode active material according to any one of claims 1 to 12, or a positive electrode active material prepared by the preparation method of the positive electrode active material according to claim 13.
15. A battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 14.
16. An electrical device, characterized in that: Comprising the battery of claim 15.